Dermatopatología en cabras con fotosensibilización por Heterophyllaea pustulata: Estudio histopatológico secuencial - Micheloud, Juan Francisco (2019)
Photosensitization dermatitis is a frequent skin disorder in animals and humans that occurs when photodynamic or fluorescent pigments are deposited in sunlight-exposed skin. The effects of solar radiation on the integument have been known for years, and numerous studies put focus on the direct effects of sun or UV radiation on the cutaneous tissue. However, most of the dermatopathological studies refer to a few natural cases, whereas there are no sequential and/or experimental studies on cutaneous lesions produced by photosensitizing substances. Anthraquinones (AQs) are a group of photoactive substances present in some plants, and several of them have been identified in Heterophyllaea pustulata Hook f. (Rubiaceae). This vegetal species has demonstrated photosensitizing activity in natural and experimental cases. This work shows sequenced skin lesions present on goats experimentally intoxicated with H. pustulata over time. In addition, proliferation and cell death patterns are shown by immunohistochemistry.